PHYSICAL DEVELOPMENT AND PHYSICAL FITNESS OF 8-YEAR-OLD STUDENTS - Mariana Borukova (Scientific Publishing House. NSA Press, 2023)
Human physical development is a complex and intricate concept that can be viewed as a dynamically changing state from the moment of birth till death. The purpose of this study was to determine the level of physical development and physical fitness of 8-year-old students and to apply a comparative analysis along the factor gender. The study sample consisted of 95 primary school students (44 boys and 51 girls) in the city of Varna. The applied methods were a review study of specialized literature and sports-pedagogical testing along 18 indicators that carry information about the children's physical development and some motor qualities. Mathematical-statistical data were processed by means of variation and comparative analyses, which gave us grounds to assert that the differences obtained from all indicators that carry information about physical development and physical fitness, the advantage was in favor of the boys. For three of the characteristics, the differences were statistically significant.